Perceived Bonding by Parents Living With HIV and Their Adolescent Children. (31st October 2015) - Li, Li; Liang, Li‐Jung; Ji, Guoping; Lin, Chunqing; Xiao, Yongkang
Abstract : This study examined the associations between parent and adolescent reports of bonding within families and the relationships among reported parental bonding, family conflict and adolescent stress. A total of 118 families from Anhui, China, were recruited for this study. Two family‐level bonding scores were constructed: the average of and difference between parent and adolescent bonding scores. Study results indicated that the difference between parent and adolescent bonding reports was associated with higher levels of adolescent daily stress. A negative association was observed between average family‐level bonding and the level of parent‐reported conflict. Our findings highlight the importance of combining data from both parents and adolescents when studying issues related to family wellbeing.